Combination of the Herbs Radix Rehmanniae and Cornus Officinalis Mitigated Testicular Damage From Diabetes Mellitus by Enhancing Glycolysis via the AGEs/RAGE/HIF-1α Axis - Chen, Yuping; Chen, Jing; Shu, Anmei; Liu, Liping; Wu, Qin; Wu, Juansong; Song, Siyuan; Fan, Weiping; Zhu, Yihui; Xu, Huiqin; Sun, Jihu; Yang, Liucai (Frontiers in Pharmacology, 2021)
Radix Rehmanniae and Cornus Officinalis (RR-CO) have been widely used as “nourishing Yin and tonifying kidney” herb pairs for the treatment of diabetes mellitus (DM) and its complications in traditional Chinese medicine (TCM). Based on the theory of “kidney governing reproduction” in TCM, the aim of this study was to investigate the therapeutic effects of RR-CO on DM-induced reproduction damage through regulating testicular glycolysis. Moreover, the regulation of AGEs/RAGE/HIF-1α axis on the testicular glycolysis process has also been studied. Spontaneous DM model KK-Ay mice were used to investigate the protective effect of RR, CO, RR-CO on DM-induced reproductive disturbances. RR, CO, RR-CO improved DM-induced renal and testicular morphology damages. Moreover, the impaired spermatogenesis, germ cell apoptosis and motility in testis induced upon DM were also attenuated by RR, CO or RR-CO, accompanied by an increased level of glycolysis metabolomics such as L-lactate, D-Fructose 1,6-bisphosphate, etc. Meanwhile, glucose membrane transporters (GLUT1, GLUT3), monocarboxylate transporter 4 (MCT4) expression, lactate dehydrogenase (LDH) activity, HIF-1α were upregulated by RR, CO and RR-CO treatment compared with the model group, whereas AGE level and RAGE expression were decreased with the drug administration. The RR-CO group was associated with superior protective effects in comparison to RR, CO use only. Aminoguanidine (Ami) and FPS-ZM1, the AGEs and RAGE inhibitors, were used as a tool drug to study the mechanism, showing different degrees of protection against DM-induced reproductive damage. This work preliminarily sheds light on the herb pair RR-CO exhibited favorable effects against DM-induced reproductive disturbances through enhancing testicular glycolysis, which might be mediated by AGEs/RAGE/HIF-1α axis.